The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1002/path.4432
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis dysregulates MMP/TIMP balance to drive rapid cavitation and unrestrained bacterial proliferation

Abstract: Active tuberculosis (TB) often presents with advanced pulmonary disease, including irreversible lung damage and cavities. Cavitary pathology contributes to antibiotic failure, transmission, morbidity and mortality. Matrix metalloproteinases (MMPs), in particular MMP-1 are implicated in TB pathogenesis. We explored the mechanisms relating MMP/TIMP imbalance to cavity formation in a modified rabbit model of cavitary TB. Our model results in consistent progression of consolidation to human-like cavities (100% by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
85
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 45 publications
4
85
1
8
Order By: Relevance
“…Cavities may contain many neutrophils. Recent publications report that neutrophils and proteases contribute to the softening and fragmentation that leads to cavitation 7, 62, 74, 75 . While this may be true, the data are not convincing because investigators have not been able to study developing post primary TB.…”
Section: Discussionmentioning
confidence: 99%
“…Cavities may contain many neutrophils. Recent publications report that neutrophils and proteases contribute to the softening and fragmentation that leads to cavitation 7, 62, 74, 75 . While this may be true, the data are not convincing because investigators have not been able to study developing post primary TB.…”
Section: Discussionmentioning
confidence: 99%
“…15 In presensitised rabbits, MMP-1 has been shown to have a causal role in pulmonary cavitation. 27 Specifically, the development of cavities within areas of dense consolidation has been associated with MMP-1/ TIMP imbalance and high intracavitary bacterial burden. In human TB granulomas, MMP-1 expression is upregulated 606-fold compared with uninfected lung.…”
Section: Discussionmentioning
confidence: 99%
“…The well-suited model for cavitation, the rabbit, has been reinvestigated [177], and provides compelling evidence that matrix-degrading enzymes are essential for progression of dense consolidated lesions-which are distinct from granulomas-to cavitation [177]. Studies in guinea pigs [178] and mice [179][180][181] further indicate that breakdown of lung collagen is essential for necrosis, which likely precedes cavitation.…”
Section: The Way Out: the Tb Cavitymentioning
confidence: 98%
“…Paucity of lymphocytes likely explains massive bacillary replication at the cavity wall [60]. However, in animal models, strength of the DTH correlates with cavity formation [59,189] and with the protease imbalance [177]. Adoptive cell transfer studies in the TDM-induced granuloma model have indicated a major role of the CD4 + T lymphocytes in induction of tissue injury [190].…”
Section: The Way Out: the Tb Cavitymentioning
confidence: 98%
See 1 more Smart Citation